Silence can be golden: On the value of allowing managers to keep silent when information is soft - Versano, Tsahi (Journal of Accounting and Economics, 2021)
Most information that public firms are required to disclose is relatively hard (e.g., historical information), whereas the disclosure of relevant information that is softer in nature (e.g., forward-looking information) is typically left to firms' discretion. The lack of a mandatory requirement to disclose soft information has been at the heart of a number of on-going accounting debates. This study shows that while mandating disclosure increases the frequency of disclosure, it results in a reduction in disclosure quality when information is soft. By exploring this tradeoff, the paper sheds light on the merits of restricting mandatory disclosure requirements to verifiable information and leaving disclosure of soft information unregulated. The value of leaving disclosure unregulated is shown to be maximized when managers are given bonus-based compensation, with minimum performance thresholds and maximum caps, similar to those documented in the literature.